Effects of climatic elements on Campylobacter-contaminated chicken products in Japan - Ishihara, K.; Takahashi, R.; Andoh, M.; Makita, K.; Kamiji, S.; Ueno, H.; Muramatsu, Y.; Tamura, Y. (Cambridge University Press, 2012)
Japanese weather data for areas that produced Campylobacter spp.-positive chicken products were compared with those for areas producing negative samples. Regarding samples produced during the period of rising temperature (spring and summer), the mean weekly air temperatures for Campylobacter-positive samples were higher than those for negative samples for the period of the week in which the samples were purchased (18·7°C vs. 13·1°C, P=0·006) to a 12-week lag (12 weeks before purchasing samples; 7·9°C vs. 3·4°C, P=0·009). Significant differences in weekly mean minimum humidity and sunshine duration per day were also observed for 1- and 2-week lag periods. We postulated that the high air temperature, high humidity and short duration of sunshine for the chicken-rearing period increased Campylobacter colonization in chickens during the period of rising temperature. Consequently, the number of Campylobacter-contaminated chicken products on the market in Japan may fluctuate because of the climatic conditions to which reared chickens are exposed.